Construction and preparation of novel 2D metal-free few-layer BN modified graphene-like g-C3N4 with enhanced photocatalytic performance. Issue 34 (11th August 2017) - Gu, Jiemin; Yan, Jia; Chen, Zhigang; Ji, Haiyan; Song, Yanhua; Fan, Yamin; Xu, Hui; Li, Huaming
Abstract : Novel two-dimensional (2D) metal-free few-layer BN/graphene-like g-C3 N4 (2D BN/g-C3 N4 ) composites have been synthesized by a simple hydrothermal method. Abstract : Novel two-dimensional (2D) metal-free few-layer BN/graphene-like g-C3 N4 (2D BN/g-C3 N4 ) composites have been synthesized by a simple hydrothermal method. The construction of a 2D/2D structure between BN and g-C3 N4 could shorten the migration distance of charge transfer, and provide a large contact surface. By introducing few-layer BN nanosheets into g-C3 N4, the as-prepared 2D BN/g-C3 N4 composites exhibited a much enhanced photocatalytic performance than that of pure g-C3 N4 . The 0.5% 2D BN/g-C3 N4 composite possessed the most wonderful ability towards Rhodamine B (RhB) degradation irradiated by visible light, which could achieve a highest degradation efficiency of 98.2% within 120 min. Further studies revealed that modifying g-C3 N4 with few-layer BN could not only facilitate the separation and transfer of photo-induced holes and electrons, but also exposed the fact that the (002) facet edges of BN terminated with –OH groups could act as catalytic sites, and thus enhance the photocatalytic activities. Moreover, the successful preparation of 2D BN/g-C3 N4 composites may pave the way for fabricating other 2D composites with a layer-by-layer architecture.